The Calama-Olacapato-El Toro fault system in the Puna Plateau, Central Andes: Geodynamic implications and stratovolcanoes emplacement - Norini, Gianluca (2013)
The structural evolution of the Puna Plateau is characterized by the activity of both orogen-parallel and orogen-oblique faults. Understanding the possible relationship between these two structural styles, their geodynamic implications and the influence on the migration of magmas is important to get insights into the tectonic and magmatic evolution of the Central Andes. In this study, we present a structural analysis of the orogen-oblique Calama-Olacapato-El Toro fault system and the surrounding orogen-parallel thrust faults in the central-eastern Puna Plateau. Morphostructural analysis and field mapping reveal the geometry, kinematics and dynamics of the tectonic features in the studied area. We propose a three-dimensional geometrical reconstruction of the main fault planes showing their attitude and intersections at depth. The study indicates that the crust underwent simultaneous deformation along both the vertical transcurrent Calama-Olacapato-El Toro fault system and the low-angle thrust faults, and that the back-arc portion of the Calama-Olacapato-El Toro fault system developed as a transfer zone among the main N-striking thrusts. Our model considers that both orogen-parallel and orogen-oblique fault systems should be regarded as parts of the same tectonic system, accommodating crustal shortening of a thickened crust. The study suggests that the tectonic control on the magma and fluid circulation in the crust is mainly related to the geometry of the fault planes and the orientation of the stress field, with a previously unrecognized important role played by the orogen-parallel thrust faults on the emplacement of the stratovolcanoes.